PENERAPAN PENGUMUMAN IDENTITAS PELAKU KEKERASAN SEKSUAL TERHADAP ANAK - Feren Nabilla (2022)
Based on the results of the Online Information System for the Protection of Women and Children for the 2020 period, news related to sexual violence against children reached 5,640 cases. The number of cases of sexual violence against children, the government stipulates Government Regulation Number 70 of 2020 regarding the implementation of additional criminal arrangements for perpetrators of sexual violence against children. This determination has sparked a polemic among the community, especially with the inclusion of additional penalties in the form of announcing the identity of the perpetrator. The scope of research regarding the urgency of the additional punishment in the form of announcing the identity of the perpetrator and the application of this additional punishment in Indonesian criminal justice. The purpose of this study is to identify the urgency of the enactment of Government Regulation Number 70 of 2020. The research method applied to analyze and answer legal issues in this article uses the normative juridical method. The results of the study show that sexual violence against children can be classified as a serious, cruel crime or can be known as graviora delicta so that perpetrators can be subject to additional punishment in the form of announcing the identity of the perpetrator as contained in Government Regulation No. 70 of 2020.